Autochthonous microorganisms as an alternative for the biofertilization of Glycine max (L.) Merrill - Ceiro Catasú, Wilson Geobel (2023)
Introduction. Soybean (Glycine max (L.) Merrill) has economic and nutritional importance due to its protein levels and vegetable oil content of biological quality, necessary for human and animal feed. The microbial alternatives for biofertilization of this crop would represent an option for its production with low inputs in tropical conditions. Objective. To evaluate the effect of autochthonous microorganisms (MA) as an alternative for biofertilization of G. max under low-input production conditions. Materials and methods. The experiment was established in a farm located in the town of El Coco, Yara, Granma, Cuba, on a Carbonated Fluffy Brown soil, during the year 2021. Certified G. max cv. Incasoy-27 seeds were used. Sowing was carried out in spring at a distance of 0.70 m x 0.04 m. Three doses of MA (12, 24, and 36 L ha-1) and an absolute control where used. Variables of growth, yield, and their components were evaluated. A randomized block design was used. Data were processed by ANOVA, linear regression, correlation, and principal component analysis. Results. The MA biostimulated the growth of G. max in a range of 12 % and 24 %, while the yield was favored between 16 % and 44 %. Pearson’s correlation analysis indicated that the seeds mass per plant and number of pods per plant were the variables most strongly interrelated with yield. Conclusion. The inclusion of MA achieved a biostimulation of plants length growth of G. max cv. Incasoy-27 compared to the control and the agricultural yield was enhanced.